PERANCANGAN SISTEM INFOPRMASI APOTEK PHARFACILLE BERBASIS WABSITE DENGAN TIGA TAHAP METODE AGAILE - I Kadek , Krisna Angga Pamungkas; Moch , Anwar Fery Rais; I Gede, Irvan Pramanta Andika (Journal Pharmactive, 2026)
The development of information technology has driven digital transformation across various sectors, including pharmaceutical services in pharmacies. Common problems faced by pharmacies that still rely on manual systems include inaccurate stock recording, delays in report generation, and low service efficiency. This study aims to design and develop a web-based pharmacy information system named PHARFACILLE to improve the effectiveness and accuracy of pharmacy operational management. The method used in this study is the Software Development Life Cycle (SDLC) combined with the Agile approach using the Scrum framework. System development was carried out iteratively through several sprints, covering planning, analysis, design, implementation, and evaluation stages. System modeling was conducted using Unified Modeling Language (UML) to describe system requirements and process flows. The results show that the PHARFACILLE system was successfully developed with main features including user authentication, sales dashboard, cashier system, inventory management, ordering and goods receiving management, and financial reporting. Integration between modules enables real-time data updates, thereby improving stock accuracy and transaction efficiency. Based on the development results, this system has the potential to enhance pharmacy service quality, accelerate operational processes, and support managerial decision-making through more accurate and structured data presentation.